EFEKTIVITAS BAWANG PUTIH (Allium sativum L) UNTUK MENINGKATKAN KETAHANAN TUBUH IKAN MAS (Cyprinus carpio L) TERHADAP PENYAKIT Motile Aeromonas Septicemia - , Iesje Lukistyowati, Dra.,MS.; , Prof. drh. Kurniasih, MV.Sc., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The aim of the research ware to investigate and discover the effectiveness of fresh Lumbu hijau (type of garlic) given by ten-minute immersion and Kating (type of garlic) extract mixed with feed in enhancing common carpâs immunity against Motile Aeromonas Septicemia. The research results showed that Kating was the most highly effective in inhibiting the growth of A. hydrophila in comparison with the other type of garlic. The inhibition diameter of the garlic against A. hydrophila was 17.00Â±20.00 mm. A test of the active components of Kating using the spectrometrical chromatography method (GC-MS) detected as many as 13 components, one of which was diallyl disulfide with antimicrobial activity found with area of 16.95%, whereas a test using thinlayered chromatography detected saponin with antimicrobial activity. A minimum inhibitory concentration (MIC) test of a squeeze of Lumbu hijau on A. hydrophila showed a minimum concentration of 6.13-3.63% (61,300 ppm-36,300 ppm). The LC50 the garlic on common carp immersed for ten minutes was 4,913.99 ppm whereas 24-hour immersion gave a LC50 of 846.75 ppm. Research for preventing and curing MAS by ten-minute immersion was conducted four times in four days interval. A completely random design in triplicate (10 fishes/replication) was use in this experiment. The doses administered were : P0, P1 (1.000 ppm), P2 (2.000 pm) and P3 (3.000 ppm). At the end of the research, the fish were intraperitoneally infected with A. hydrophila with a density of 108 cell/ml in a dose of 0.1 ml/fish. The research result demonstrated that the survival rate of fish immersed in a squeeze of Lumbu hijau was higher than that of the control group (P<0,05). The best dose to encrease the survival rate by ten-minute immersion was 1826 ppm. Treatment by ten-minute immersion was not effective as the survival rate of treated fish was lower than that of the control (P>0,05) because the MIC value was greater than the LC50 value. Pathological changes occurred on the epidermis : the skin underwent erosion, hemorrhage, and degeneration